Analisis Perencanaan Kebutuhan Material Proyek dengan Metode Material Requirement Planning - Yuni Wibawanti (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2019)
Project for making transfer towers as part of the conveying system project. The implementation of this project involves various types of material needed. Because the project implementation time is limited, it is necessary to carry out the project properly so that the project runs smoothly and is completed on time. In this study an analysis of project material inventories was carried out by applying the Material Requirement Planning (MRP) method. The research objective is to determine the technique of ordering the right material so that the project implementation runs smoothly. From the results of the analysis carried out, it was found that the size of ordering materials using the lot sizing technique Part Period Balancing would incur costs of IDR 203,515,797.82. Costs incurred are smaller than Lot for Lot techniques.